Regenerating tubular epithelial cells of the kidney. Issue 11 (15th July 2020) - Stamellou, Eleni; Leuchtle, Katja; Moeller, Marcus J
Abstract: Acute tubular injury accounts for the most common intrinsic cause for acute kidney injury. Normally, the tubular epithelium is mitotically quiescent. However, upon injury, it can show a brisk capacity to regenerate and repair. The scattered tubular cell (STC) phenotype was discovered as a uniform reaction of tubule cells triggered by injury. The STC phenotype is characterized by a unique protein expression profile, increased robustness during tubular damage and increased proliferation. Nevertheless, the exact origin and identity of these cells have been unveiled only in part. Here, we discuss the classical concept of renal regeneration. According to this model, surviving cells dedifferentiate and divide to replace neighbouring lost tubular cells. However, this view has been challenged by the concept of a pre-existing and fixed population of intratubular progenitor cells. This review presents a significant body of previous work and animal studies using lineage-tracing methods that have investigated the regeneration of tubular cells. We review the experimental findings and discuss whether they support the progenitor hypothesis or the classical concept of renal tubular regeneration. We come to the conclusion that any proximal tubular cell may differentiate into the regenerative STC phenotype upon injury thus contributing to regeneration, and these cells differentiate back into tubular cells once regeneration is finished.